A soil-carrying lacewing larva in Early Cretaceous Lebanese amber. Issue 1 (December 2018) - Pérez-de la Fuente, Ricardo; Peñalver, Enrique; Azar, Dany; Engel, Michael
Abstract Diverse organisms protect and camouflage themselves using varied materials from their environment. This adaptation and associated behaviours (debris-carrying) are well known in modern green lacewing larvae (Neuroptera: Chrysopidae), mostly due to the widespread use of these immature insects in pest control. However, the evolutionary history of this successful strategy and related morphological adaptations in the lineage are still far from being understood. Here we describe a novel green lacewing larva, Tyruschrysa melqart gen. et sp. nov., from Early Cretaceous Lebanese amber, carrying a preserved debris packet composed by soil particles entangled among specialised setae of extremely elongate tubular tubercles. The new morphotype has features related to the debris-carrying habit that are unknown from extant or extinct green lacewings, namely a high number of tubular tubercle pairs on the abdomen and tubular tubercle setae with mushroom-shaped endings that acted as anchoring points for debris. The current finding expands the diversity of exogenous materials used by green lacewing larvae in deep time, and represents the earliest direct evidence of debris-carrying in the lineage described to date. The debris-carrying larval habit likely played a significant role during the initial phases of diversification of green lacewings.